Proposed new interior design of spa for Jamu Mak Dara Sdn. Bhd. at No. 5 Lengkok Harimau, Jalan Sultan Azlan Syah, 30450 Ipoh Perak / Nasihah Bazilah Abdull Latib - Abdull Latib, Nasihah Bazilah (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is Proposed New Interior Design of Spa for Jamu Mak Dara sdn. bhd. at No. 5 Lengkok Harimau, Jalan Sultan Azan Syah, 30450 Ipoh Perak. This proposed spa is to attract users, mostly on women to try for themselves the treatment that Jamu Mak Dara sdn. bhd. offered, at the same time to promote their product successfully as they offered a malay-based treatment and interiors, that is truly different from other spa range, that comes mostly from Thailand and Indonesia. The target market for the u|er of this spa range from women and mep from all ages and races, who are concern ajsout th^ir look and appearances, not forgetting to find those who are interested in trying sr malay-based sjwrtreatment. Because of the customers that attend the sessions comes from different class of people, each room should be different so that it would match with the customers’ needs and it could give comfort to them while attending the sessions. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the faith in the customers and the workers in Jamu Mak Dara Spa. The chosen design style for Jamu Mak Dara Spa is based on Modem Malay Tropical design, it goes all the way with the client’s needs as they want the spa have the modem malay look and at the same time would attract the customers with different image that they would only get in Jamu Mak Dara Spa. Before getting a desired design that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of customers to attend the session, types of services offered, products of the brand, spaces to be required in the proposed area, operation time and informations about other spas that use the same system in management, as the proposed spa. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.